THE EFFECT OF HEALTH EDUCATION THROUGH THE PEER GROUP METHOD ON THE INTEREST OF ADOLESCENT GIRL IN PRIMARY PREVENTION OF CERVICAL CANCER AT SENIOR HIGH SCHOOL DHARMA WANITA 4 TAMAN SIDOARJO - Suryaningsih, Merlyna (NHM PRESS, 2085)
Cervical cancer is the second most common type of malignant tumor in theworld that causes death. Lack of information about primary prevention of cervicalcancer causes low interest in adolescents girls. The results of a preliminary studyof 10 students, found 55% of students had less interest in primary prevention ofcervical cancer. Efforts to increase interest in health education through peergroup methods. The purpose of the study was to analyze the effect of healtheducation through the Peer Group method on the interest of young women inprimary prevention of cervical cancer in SMA Dharma Wanita 4 Taman Sidoarjo.Research Design Quasy Experiment pre-test control design approach. Theindependent variable is Health education through the peer group method, thedependent variable is interest. The population is grade X, XI students at DarmaWanita 4 Taman Sidoarjo. A sample of 32 students was taken by simple randomsampling. The instrument was a questionnaire, tested by t paired and independentt test with a significance level of 0.05. This research has been carried out ethicalclearance test by KEPK STIKes Ngudia Husada Madura.Intervention group research results there was an increase in interestaverage of 7,438, using paired t test obtained ? value = (0.001 <0.05), meaningthere was an influence of providing education on interest in primary prevention ofcervical cancer, in the control group there was an average increase interest of1.063, paired t test obtained ? value = 0.359, meaning there is no difference ininterest adolescent girls regarding primary prevention of cervical cancer beforeand after treatment. Independent t test results obtained ? value = (0.003 <0.05),meaning that there were differences in the interests of adolescent girls in theintervention and control groups.It is expected that young women will take part in health education throughthe peer group method because it is very effective in increasing the interest ofadolescents, health workers can conduct health education through peer groupmethods on a regular basis regarding reproductive health